Pengaruh Komunikasi Antarbudaya terhadap Integrasi Sosial Masyarakat Desa Simpang Rantau Gedang Jambi - Nur, Meilani; Ayunda Rahmawati, Dayyinah (CV. AKIRA JAVA BULU, 2025)
This quantitative research aimed at examining the influence of intercultural communication on social integration within the community of Simpang Rantau Gedang Village, a multi-ethnic village located in Batanghari Regency, Jambi Province. The method used is a survey with an explanatory approach, involving 30 purposively selected respondents, residents from diverse cultural backgrounds who participate in the village's social life. Data collection was conducted through a questionnaire based on five-point Likert scale. The research instrument was tested for validity using Pearson correlation and for reliability using Cronbach’s Alpha coefficient. The collected data were analyzed using descriptive and inferential statistics, with a simple linear regression test performed using SPSS 24. The results show that intercultural communication has a positive and significant effect on social integration. The highest correlation indicators include involvement in cultural discussions and understanding of shared values, indicating the importance of open and respectful communication in strengthening social cohesion amid diversity. Based on the findings, it is recommended that village governments enhance intercultural dialogue forums and organize cross-ethnic collaborative activities to foster mutual understanding and reinforce social solidarity. Effective intercultural communication should be established as a fundamental strategy for inclusive and sustainable village empowerment and development.